The Effect of the Blended Learning Model on Student Critical Thinking Skill: Meta-analysis - Wiwid Suryono; Bambang Bagus Haryanto; Tomi Apra Santosa; Abdul Rahman; Yayat suharyat; Baso Intang Sappaile (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to investigate the effect of blended learning learning models on students' critical thinking skills: meta-analysis. This research is a meta-analysis research. The source of the data in this study came from an analysis of 10 national and international journals published from 2015-2023. Data source tracking through Google Scholar, ScienceDirect, Wiley, ProQuest and Sage. The inclusion criteria in the study are 1) published articles must be indexed by SINTA and Scopus; 2) Research must be experimental or quasi-experimental; 3) the article has data that can be calculated by the value of the effect size (ES). Data analysis in this research is a quantitative analysis by calculating the effect size value of each article with the help of the JSAP application. The results showed that the average effect size was 0.79 with moderate criteria. These findings indicate that the blended learning learning model has a significant influence on students' critical thinking skills. The blended learning model helps students grow their critical thinking skills when studying.